Suitability of the Hanging Meniscus RDE for the Electrochemical Investigation of Ionic Liquids. Issue 4 (28th February 2020) - Wippermann, K.; Suo, Y.; Korte, C.
Abstract : Employing the oxygen reduction reaction (ORR) exemplarily, the suitability of the hanging meniscus RDE (HMRDE) technique for viscous electrolytes—in particular for ionic liquids—was examined. RDE and HMRDE experiments were carried out using polycrystalline Pt disks in contact with either concentrated phosphoric acid, N, N-diethylmethylammoniumtriflate ([Dema][TfO]) or 2-sulfoethylmethyl-ammoniumtriflate ([2-Sema][TfO]). RDE measurements revealed Levich factors of the oxygen transport close to the theoretical value, even if the thickness of the hydrodynamic layer was about ⅔ of the disk diameter. HMRDE experiments showed a pronounced scattering of the Levich factors, which means a significant error in the determination of the mass transport parameters. In contrast, reliable Tafel factors of ORR were obtained from HMRDE experiments with viscous mixtures of [2-Sema][TfO] and water. The thickness of the perturbed layer δ pl near the edge of the HMRDE was found to be virtually independent of the viscosity of the respective electrolyte. In the case of viscous electrolytes like ionic liquids, the HMRDE technique is particularly suitable for investigating the kinetic parameters of electrochemical processes at elevated temperatures >100 °C, whereas a more precise determination of mass transport properties will only be possible once the experimental error can be significantly reduced.